PENGUJIAN KETELITIAN GEOMETRIK MESIN POTONG PELAT LOGAM DENGAN PENGARAH PISAU PARALEL DENGAN MENGGUNAKAN SNI 05-1192-1989 - Bimbing Atedi,; Djoko Agustono; Zainulsyah Zainulsyah (JURNAL STANDARDISASI, 2006)
Testing of the geometrical accuracy of machine tool is one of the important factors in order to know whether the machine can produce a product that fulfills the technical requirement. A testing of shearing machine with parallelism guidance tools was conducted in this research. Testing was carried out based on SNI 05-1192-1989 about the method of testing of accuracy of shearing machine in the final state or without any load. The testing comprised of leveling, tool parallelism, guidance slot and thickness tools frame and the parallelism lower tool and faces limit. The result of the testing shows that those are some deviations which might be caused by the wear of the components. The geometrical deviation has exceeded the tolerance limit; it means that some improvement steps are needed. One of the improvement steps is re-set the machine. Another alternative is using the machine only for producing a lower accuracy product.